The Perspective of Dysregulated LncRNAs in Alzheimer's Disease: A Systematic Scoping Review - Asadi, Mohammad Reza; Hassani, Mehdi; Kiani, Shiva; Sabaie, Hani; Moslehian, Marziyeh Sadat; Kazemi, Mohammad; Ghafouri-Fard, Soudeh; Taheri, Mohammad; Rezazadeh, Maryam (Frontiers in Aging Neuroscience, 2021)
LncRNAs act as part of non-coding RNAs at high levels of complex and stimulatory configurations in basic molecular mechanisms. Their extensive regulatory activity in the CNS continues on a small scale, from the functions of synapses to large-scale neurodevelopment and cognitive functions, aging, and can be seen in both health and disease situations. Alzheimer’s as a neurodegenerative disease is one of the effects of the pathological role of dysregulated LncRNAs in the CNS. The disease is characterized by two main hallmarks: amyloid plaques due to the accumulation of β-amyloid components and neurofibrillary tangles (NFT) resulting from the accumulation of phosphorylated tau. Numerous studies in humans, animal models, and various cell lines have revealed the role of LncRNAs in the pathogenesis of Alzheimer’s disease. This scoping review was performed with a six-step strategy and based on the Prisma guideline by systematically searching the publications of 7 databases. Out of 1591 records, 69 articles were utterly aligned with the specified inclusion criteria and were summarized in the relevant table. Most of the studies were devoted to BACE1-AS, NEAT1, MALAT1, and SNHG1 LncRNAs, respectively, and about one-third of the studies of a unique LncRNA were studied. About 56% of the studies were associated with up-regulation and 7% with down-regulation of LncRNA expression. Overall, this study was conducted to investigate further the association between LncRNAs and Alzheimer’s disease to be a reputable source for further studies and find more molecular therapeutic goals for this disease.